2007
DOI: 10.1111/j.1469-0691.2007.01700.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological testing for Bartonella henselae infections in The Netherlands: clinical evaluation of immunofluorescence assay and ELISA

Abstract: Cat-scratch disease (CSD), caused by Bartonella henselae infection, can mimic malignancy and can manifest atypically. Reliable serological testing is therefore of great clinical importance. The diagnostic performance of immunofluorescence assay (IFA) and ELISA was evaluated in a group of Dutch patients with proven CSD (clinical diagnosis confirmed by PCR). Sera of 51 CSD patients and 56 controls (patients with similar symptoms, but who were B. henselae PCR-negative and had an alternative confirmed diagnosis) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
64
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 28 publications
2
64
0
3
Order By: Relevance
“…The collection of serum occurred 0-17 days (median 5 days) before tissue sampling. A 'control' group consisted of 50 patients (mean age 35 years) who were clinically suspect for CSD but tested negative for B. henselae IgM antibodies using an in-house-prepared immunofluorescence assay as described previously (Bergmans et al, 1997;Vermeulen et al, 2007). A real-time PCR assay targeted at the heat-shock protein groEL was used to detect B. henselae DNA in all serum samples (Diederen et al, 2007a).…”
mentioning
confidence: 99%
“…The collection of serum occurred 0-17 days (median 5 days) before tissue sampling. A 'control' group consisted of 50 patients (mean age 35 years) who were clinically suspect for CSD but tested negative for B. henselae IgM antibodies using an in-house-prepared immunofluorescence assay as described previously (Bergmans et al, 1997;Vermeulen et al, 2007). A real-time PCR assay targeted at the heat-shock protein groEL was used to detect B. henselae DNA in all serum samples (Diederen et al, 2007a).…”
mentioning
confidence: 99%
“…The presence of IgM in patients is clear evidence of recent contact with B. henselae; however, the sensitivity of assays in the detection of the IgM is low (5)(6)(7)(8)(9)(10)12). IgM remains in the serum for approximately 3 months (7,13). The development of a more sensitive as well as more specific IgM assay for B. henselae is crucial for improving the clinical diagnosis of CSD.…”
Section: Discussionmentioning
confidence: 99%
“…We proved that the ELISAs using antigen II, IV, and V could clearly distinguish between the two sets of sera, whereas the ELISAs with antigen I and III showed overlapping results for the two sets, indicating that these two antigens were not suitable for use in the IgM-ELISA. There have been many previous reports on the development of IgM-ELISAs using whole-cell protein (antigen I) (6)(7)(8)(9)(10), which have generally shown poor sensitivity. We confirmed that whole-cell protein was inappropriate for use in the IgM-ELISA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations